Relevansi Materi Pendidikan Karakter Sosial dalam Zul Ishba' dengan Nilai-Nilai Islam - Damhuri Damhuri (Al-Ulum, 2019)
This article aims to depict the material of social character education in the will, Zul Ishba 'al-Adwani and explain its relevance to Islamic values. The research results show that the interpretation of jahiliyah terminology, which is identical with moral decline, is not all true. Each community has a value that is a reference in social interaction. This is reflected in the will of Zul Ishba 'al-Adwani, a figure of the jahiliyah era, who is loaded with moral values ​​in the context of social interaction. 'Al-Adwani considers that to acquire appreciation in society, one does not have to act arrogantly, but is obtained by first anesthetizing their hearts with commendable qualities, such as tenderness, humble, generous, and always responding to their interests. Although Zul Ishba' lived during the pre-Islamic era, the material in his determination has relevance to the character values ​​in Islam. The character shows that there is a universal value recognized by all societies without being limited by ideological differences.